Information Search, Integration, and Personalization International Workshop, ISIP 2013, Bangkok, Thailand, September 16--18, 2013. Revised Selected Papers - Kawtrakul, Asanee.; Kawtrakul, Asanee.; Laurent, Dominique.; Laurent, Dominique.; Spyratos, Nicolas.; Spyratos, Nicolas.; Tanaka, Yuzuru.; Tanaka, Yuzuru. (Communications in Computer and Information Science, 2014)
This book constitutes the refereed post-proceedings of the International Workshop on Information Search, Integration and Personalization, ISIP 2013, held in Bangkok, Thailand, in September 2013. The 10 revised full papers presented were carefully reviewed and selected from 28 presentations. The papers are organized in topical sections on knowledge federation and integration; information discovery; recommendation systems and ontologies.